Vicinal combination of N—NH2 and C—NO2 benefitting for low sensitivity and high energy azole molecules: A strategy developed from isomerization - Yao-yao Linghu; Chao-yang Zhang (Energetic Materials Frontiers)
It is nowadays challenging to create low sensitivity and high energy molecules (LSHEMs), largely restricted by the high complexity and difficult interpretation of composition-structure-property relationships of energetic materials. In the present theoretical modeling work on energetic materials, we propose a strategy for constructing LSHEMs based on energetic azole isomerism to reduce the molecular complexity while maintain composition. That is, we firstly find that the vicinal combination of N—NH2 and C—NO2 is an effective unit to enhance both energy and molecular stability of azoles. The advantage of the combination largely stems from the oxygen balance improvement to be close to zero to elevate reaction heat and packing density, and the intramolecular hydrogen bond formation to enhance molecular stability. Thus, this unit can be widely considered in constructing N-rich low sensitivity and high energy azole molecules. In addition, we confirm that the N—NO2 generally seriously do harm to the molecular stability of azoles, especially in the case of the existence of steric effect around it.